1974
DOI: 10.1099/00221287-82-1-49
|View full text |Cite
|
Sign up to set email alerts
|

Further Studies on Corynebacterium Species Capable of Producing Diphtheria Toxin (C. diphtheriae, C. ulcerans, C. ovis)

Abstract: Corynebacterium ulcerans and C. ovis. In addition to diphtheria toxin, lysogenic C. ulcerans and C. ovis strains each produce their own specific toxin; they also maintain their specific morphology and urease production whilst C. diphtheriae strains lysogenized by C. ulcerans phagesproduce only diphtheria toxin. The majority of C. ulcerans phages are unable to induce the production of diphtheria toxin in strains of C. ulcerans.Phage typing with Corynebacterium ulcerans phages is a practical possibility. Thirtee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
35
0
1

Year Published

1982
1982
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 8 publications
3
35
0
1
Order By: Relevance
“…One survey found that 2 of 16 (13%) C. pseudotuberculosis isolates produced diphtheria toxin (135). There have not, however, been any clinical cases of diphtheria attributed to C. pseudotuberculosis infection (23).…”
Section: Introductionmentioning
confidence: 99%
“…One survey found that 2 of 16 (13%) C. pseudotuberculosis isolates produced diphtheria toxin (135). There have not, however, been any clinical cases of diphtheria attributed to C. pseudotuberculosis infection (23).…”
Section: Introductionmentioning
confidence: 99%
“…jeikeium and D2 organisms are often resistant to many antimicrobial agents (Gill et al, 1981;Soriano et al, 1987;van Bosterhaut et al, 1987). Several other species are recognised: C. ulcerans is a toxinproducing pathogen (Gilbert and Stewart, 1926-27;Maximescu et al, 1974); C . striatum (synonymous with C .…”
Section: Introductionmentioning
confidence: 99%
“…Although the production of diphtheria antitoxin may result from occasional unrecognized or inapparent infection of horses with true C. diphtheriae, C. ovis has never been found in indigenous sheep, cattle or horses in Great Britain. However, Maximescu et al (1974) have reported the isolation of 35 strains of C. ulcerans from the nasopharyngeal flora of normal horses in Romania, where 50 % of those examined were found to be carriers. Although C. ulcerans infections of the throat in man and of the mammary glands in cows are not common in the U.K., no report of the occurrence of this organism in horses has yet been published.…”
Section: Exotoxins Of C Ulcerans 175mentioning
confidence: 99%